Philosophy in colonial India - Deshpande, Sharad (Sophia Studies in Cross-cultural Philosophy of Traditions and Cultures, 2015)
This volume focuses on the gradual emergence of modern Indian philosophy through the cross-cultural encounter between indigenous Indian and Western traditions of philosophy, during the colonial period in India, specifically in the 19th and early 20th centuries.